Interpretation of English Trademark Names of Perfumery, Cosmetics and Household Chemistry: Cognitive Approach - BABINA, Ludmila Vladimirovna; DZYUBA, Ksenia Aleksandrovna (Journal of Advanced Research in Law and Economics; Vol 6 No 1 (2015): JARLE Volume VI Issue 1(11) Summer 2015, 2016)
The article touches upon interpretation of English trademark names of perfumery, cosmetics and household chemistry. The research is conducted by means of cognitive-matrix analysis which allows building a model of a complex conceptual structure called TRADEMARK. The cognitive matrix TRADEMARK consists of a core – TRADEMARK NAME – and such conceptual domains as AIM, PRODUCT and PERSON. The core of the cognitive matrix TRADEMARK contains information about the kind of a named product. Reference to the core of this cognitive structure in the process of interpretation of a trademark name presupposes, firstly, the definition of the kind of a named product and, secondly, the revelation of characteristics that may be attributed to this particular product. While interpreting a trademark name on the basis of the conceptual domain AIM, an interpreter attempts to find out the main aim that is pursued during the formation of meaning of a trademark name. To get the general idea of product characteristics that are conveyed through its name, an interpreter can apply to such cognitive contexts of the conceptual domain PRODUCT as INGREDIENTS AND SMELLS (bubble bath white lily), MANUFACTURER (eau de toilette Armani code), EFFECT (fabric stain remover Vanish Oxi Action) and PRICE (eau de toilette CHEAPANDCHIC). Interpretation of trademark names, that convey information about potential consumers of a named product, is carried out on the basis of such cognitive contexts of the conceptual domain called PERSON as OUTER QUALITIES, INNER QUALITIES, AGE, SOCIAL STATUS and GENDER.
Keywords: English trademark names of perfumery; cosmetics and household chemistry; cognitive-matrix analysis; cognitive matrix TRADEMARK; cognitive contexts; conceptual domains